European Migration Control and the Migrant Smuggling Enterprise in West Africa : Using the Concept of Biometricycle to Explain the "Corporate Smuggling" Dimensions - Iwuoha, Victor (Society, 2026)
This article discusses the European migration control system and its connection to the facilitation of migrant smuggling in West Africa. Using Nigeria’s experience, the paper explores the key developments that contributed to the expansion of the migrant smuggling business, namely, the European biometric ID systems, the digitalization of external borders, and intensive border securitization. These key measures are linked to the emergence and deepening of the operations of the new identity and document fraud cartel in Nigeria, a sub-component of the smuggling business model. I delineate a new conceptual framework, “biometric border paradox,” to depict the contradiction of the European migration control system in its external borders in Africa. The problem is linked to the new form of biometric ID and travel document fraud in corporate (government) agencies: the “corporate smugglers.” I coin two key concepts to describe this modality: “biometricycle” and “biometricyclists,” which refer to a tricycle-smuggling network that operates through the biometric ID system, involving three groups: local identity-faking entrepreneurs, IT experts, and corporate officials within the government’s biometric ID sector and immigration service. Vulnerable migrants who do not comply with the new biometric ID systems fall victim to biometric ID and travel document fraud, which exposes them to certain types of identity conflicts, state criminalization, and loss of social integration.